2022
DOI: 10.1186/s12913-022-07644-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness analysis of total laparoscopic hysterectomy versus total abdominal hysterectomy for uterine fibroids in Western China: a societal perspective

Abstract: Background As a common female pelvic tumor, uterine fibroids remain the leading cause for hysterectomy in China. Hysterectomy provides a good surgical treatment of uterine fibroids, and it guarantees the removal of all uterine fibroids without lower risk of recurrence. This study compares the cost effectiveness of total laparoscopic hysterectomy (TLH) versus total abdominal hysterectomy (TAH) for women with uterine fibroids from a societal perspective. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Most studies found no difference in the incidence of urinary tract injuries between TLH and TAH. [ 2 18 19 ] A systematic review also found a 0.14% rate of bladder or ureter injuries (122 cases) among 86,683 TLH patients. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies found no difference in the incidence of urinary tract injuries between TLH and TAH. [ 2 18 19 ] A systematic review also found a 0.14% rate of bladder or ureter injuries (122 cases) among 86,683 TLH patients. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, hysterectomy has been the most common nonpregnancy-related gynecological operation worldwide. [ 1 2 ] The standard approach is total abdominal hysterectomy (TAH). [ 1 ] However, various techniques are currently being implemented to decrease patient morbidity, caregiver burden, and inhospital stay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hysterectomy has traditionally been the primary approach for the management of symptomatic fibroids and remains the only definitive treatment available. [ 9 ] Uterine artery embolization, which is usually performed while the patient is under local anesthesia, involves temporary occlusion of the arteries supplying the uterus, with the use of biocompatible particles, to cause ischemic infarction of the fibroids. [ 10 ] As compared with hysterectomy, uterine artery embolization is associated with a shorter hospital stay and an earlier return to normal activities but also a higher likelihood of the need for additional intervention.…”
Section: Introductionmentioning
confidence: 99%